Serum Gamma-Glutamyltransferase Levels are Associated with Cardiovascular Risk Factors in China: A Nationwide Population-Based Study. Issue 1 (December 2018) - Li, Dan-Dan; Xu, Tao; Cheng, Xin-Qi; Wu, Wei; Ye, Yi-Cong; Guo, Xiu-Zhi; Cheng, Qian; Liu, Qian; Liu, Li; Zhu, Guang-Jin; Wu, Jie; Qiu, Ling
Abstract Serum gamma-glutamyltransferase (GGT), which is mainly derived from the liver, is a sensitive marker of liver cell damage and oxidative stress. More recently, it has been found that increased GGT plasma activity is also associated with cardiovascular disease (CVD). However, data on the relationship between GGT and cardiovascular risk factors (CRFs) are lacking in nationally representative samples of the Chinese population. Here, we aim to investigate both the association between GGT and CRFs and CRF clustering. A cross-sectional survey was conducted in a representative sample of 22897 adults aged 18 years and older from 2007 to 2011 nationally, which included a plurality of ethnic minorities. The participants were then divided into quartiles of sex-specific serum GGT. From the low to high GGT quartiles, the incidence of each CRF and clustered risk factors increased after adjusting for age, uric acid (UA), ethnicity, drinking, and all other risk factors. Individuals in the upper stratum (>75th percentile) had higher prevalence rates of CRFs than did those in the lower stratum (all P < 0.05). Furthermore, the subjects with clustering of 1, 2, or ≥3 CRFs were still more likely to belong to the upper GGT quartiles (75th percentiles) than were those without risk factors (all P < 0.05). In conclusion, our data highlight that there is an association between higher serum GGT levels and prevalence of CRFs, which tend to cluster with the increase in GGT activity in Chinese adults.